EP128/#847 Neo-adjuvant chemotherapy in the treatment of advanced endometrial cancer: a retrospective cohort study examining an Australian experience. (4th December 2022) - Krzys, Nicole; Nicklin, Jim
Abstract : Objectives: Neoadjuvant chemotherapy (NACT) prior to interval surgery for advanced endometrial cancer has been proposed as an alternative to primary cytoreduction (PC). We aimed to assess the oncological and surgical outcomes for women treated with NACT compared to PC for advanced EC in our unit. Methods: We performed a retrospective cohort study of women with advanced EC over a 15 year period in Queensland. NACT and PC cohorts with bulky FIGO stage IVB disease were 1:1 propensity matched for patient health status and disease histology. An ITT analysis to assess the safety and efficacy of NACT versus PC was performed. Results: 34 PC cases were 1:1 propensity matched to NACT cases. Median PFS for NACT vs PC was similar (8.6 vs 8.8 months, p-0.2) but median OS was higher in the PC cohort (16 vs 21.4 months, p0.03), despite a trend to increased RO resection in the NACT cohort (58 vs 42%, p-0.17). PC patients had higher 90 day post-operative mortality (6.5 vs 14.7%, p0.04) and accordingly NACT was associated with decreased mortality initially before survival curves crossed at 12 months. Post operative mortality in PC was offset by long-term survivors and 5 year OS (0 vs 26.5%). Conclusions: NACT was found to be inferior to PC for bulky FIGO stage IVB disease. Radical upfront surgery is associated with increased post operative mortality but also increased OS and long term cure. The prognosis of this disease is poor in both treatment groups, however, the 5 month overall survival benefit with PC was thought clinically meaningful.